Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa Melalui Model Pembelajaran Project-Based Learning - Ayu Fitriyani; Ari Septian; Sarah Inayah (https://jurnal.ysci.or.id/IME, 2025)
Understanding the concept is one of the important factors in determining student learning outcomes, if students have a good understanding of the concept it will be in line with good learning outcomes as well. This quantitative study aims to determine the improvement of students' ability to understand mathematical concepts and students' mathematical dispositions with Project-Based Learning models. This study involved 33 students (20 students of class X Nurse and 13 students of class X Pharmacy) who were positioned as research samples. Data on students' ability to understand mathematical concepts was collected using the essay test's mathematical concept comprehension ability rubric. The collected data were analyzed using descriptive statistics in the form of mean and analytical statistics in the form of independent sample t test. The results of this study inform that increasing students' ability to understand mathematical concepts using the Project-Based Learning model is better than increasing students' ability to understand mathematical concepts using ordinary learning models.